Agricultural mechanization hire services provision models, performance and challenges in Ethiopia - Tadesse, Ephrem; Tigabie, Abiro; Gizaw Desta; Sida, Tesfaye Shiferaw; Van Loon, Jelle (CIMMYT, 2025)
This report examines the structure, performance, and operational challenges of mechanization hire service provision in Ethiopia using survey data from 326 service providers across five regions. The regional distribution shows a strong concentration of service providers in Oromia, which accounts for over 60% of respondents, followed by Amhara and Central Ethiopia, while representation from Sidama remains very limited. This spatial pattern reflects both the uneven development of mechanization markets and regional differences in agricultural intensity, infrastructure, and investment. Mechanization service provision in Ethiopia is dominated by privately owned enterprises, with individual ownership model accounting for the majority of the hire services businesses. Group-based models such as cooperative unions, farmer groups, and youth groups operate at a relatively lower level. Service providers are generally middle-aged, with an average age of 43 years, and possess moderate levels of forma education, suggesting a combination of experience-based knowledge and basic technical capacity. However, female participation as individual service providers remain very low, indicating gender barriers in asset ownership, access to finance, and entrepreneurship within the mechanization sector. The experience profile of service providers points to a maturing but constrained market. 50% of the providers have more than five years of experience, indicating that mechanization hire services are well established and have operated sustainably over time. At the same time, a sizeable share entered the business within the past two to four years, reflecting earlier periods of growth and investment. Recent entry, however, appears to have slowed, likely due to rising machinery costs associated with currency devaluation and increased capital barriers. In terms of service focus, mechanization remains highly concentrated in land preparation, with limited but growing diversification into harvest and post-harvest operations such as threshing and combining. Most target client of the service providers are semi-commercial farmers, where farmers cultivate primarily small to medium-sized plots (1– 5 ha) and balance household consumption with market production. Subsistence farmers and fully commercial farms represent only a small share of clients, reflecting differences in affordability, scale, and reliance on owned machinery. Together, these patterns highlight the central role of mechanization services in supporting transitional smallholder systems rather than agricultural extremes. Despite growing demand, service provision is constrained by significant operational challenges. Machinery breakdowns, long repair times, and limited access to spare parts and fuel are widespread, reducing profitability, service reliability and limiting the capacity of providers to expand or diversify. Technology acquisition is largely driven by private investment and bank credit, with relatively limited reliance on subsidies or public support, underscoring both the entrepreneurial nature of the sector and its exposure to financial and operational risks.